The Application of FAHP on Influencing Factors Evaluation Entrepreneurial Intention of College Students - Wang, C-H; Zheng, X; Zheng, L; Lin, I-H (KnE Social Sciences, 2018)
In this article, the concept of entrepreneurial intention of college students is combed through literature review. And establishing a three dimensions and 16 criteria for the evaluation of the influencing factors of college students’ entrepreneurial intention. Next, FAHP method is used to evaluate local college students’ entrepreneurial intention. The results can improve the college entrepreneurship curriculum system, and enhance the pertinence and effectiveness of college entrepreneurship guidance. Keywords: entrepreneurial intention, FAHP, entrepreneurship guidance